Characteristics of Arun Carbonate Reservoir and Its Implication To Optimize the Most Potential Gas Resource Zone In Arun Gas Field, Aceh, Indonesia - Atmadibrata, Riza; Muslim, Dicky; Hirnawan, R. Febri; Abdurrokhim, Abdurrokhim (Indonesian Journal on Geoscience, 2019)
DOI:10.17014/ijog.6.2.209-222Since the discovery of major oil and gas reserves in carbonate rocks in the Middle East, carbonate reservoirs became important to the petroleum industry. Carbonate rocks have covered only 20% of the sedimentary rock records. However, carbonate reservoirs hold 50% of the world petroleum reserves. Arun Carbonate Reservoir is one of the biggest proven retrograde gas reservoirs in the world. After more than thirty years of production, Arun Carbonate Reservoir had an initial gas in place of 14.1 TCF residual hydrocarbon gas. The issue makes Arun Carbonate Reservoir became an interest to be studied for the development and production of hydrocarbon in other carbonate reservoirs in Indonesia. One of the fundamental topics to be studied is the characteristics of Arun Carbonate Reservoir itself. The characteristics of carbonate reservoir usually cause a lot of geologic and engineering problems in the development and production of hydrocarbon reserves. This paper aims to identify the characteristics of Arun Carbonate Reservoir and its implication to delineate the potential gas resource zone in the Arun Gas Field, Aceh, Indonesia. The data from sixteen wells have been examined through several multidiscipline studies: geophysics (well logging), geology (facies, lithology and diagenetic analyses), and petrophysics (core analysis). The result of this study shows that Arun Carbonate Reservoir (N5-N8) contains limestone 92%, 5% dolomite, and 3% dolomitic limestone (or other), and petrophysically have 16% porosity and 13.5 md permeability in average. Arun Carbonate Reservoir is divided into four facies (Reef, Near Reef, Inter Reef Lagoon, and Middle Shelf). Of four facies in Arun Carbonate Reservoir, only two facies which can be categorized as productive facies: Reef and Lagoonal Facies. The potential zones of hydrocarbon resources have vertically been documented in Arun Carbonate Reservoir.